Suction Pile Foundation Design with Finite Element Method Case Study in Madura Offshore - Dwi Puspita , Anisa
Foundation is one of the important components of the offshore platform structure which deliver the load received by the structure to the subsoil, and it is necessary to design the possible foundation that can function properly. The foundation of suction pile is one kind of foundation that is not commonly used in Indonesia but it is a promising alternative. One method that can be used to design the suction pile foundation is by using finite element method which in this study used PLAXIS 3D and PLAXIS 2D software. Used PLAXIS 3D and PLAXIS 2D software, since PLAXIS 3D software is not commonly used in Indonesia, therefore the core of this study aims to simplify the model in PLAXIS 2D. The case study location for this Final Project is located in offshore Madura with dimension of suction pile foundation: 5 m (diameter), 7.5 m (depth), and 0.05 m (thickness). Firstly, find the correction factor for simplification of 2D model with reference from Edgers et al (2008). Then the correction factor that has been obtained is used for modeling at the case study location. It is concluded that the correction factor for simplification of 2D model can be used because the ultimate strength capacity value between 2D to 3D model has small deviation value.